Jellyfish fisheries along the Gujarat coast, India: Status and challenges. (April 2023) - Kumawat, Tarachand; Saravanan, Raju; Vinod, Kavungal; Jaiswar, Ashok Kumar; Deshmukhe, Geetanjali; Shenoy, Latha; Divu, Damodaran; Joshi, Kunnummel Krishnan; Gopalakrishnan, Achamveetil
Abstract: The study exemplified jellyfish fisheries along India's Northwest coast, constituted by two emerging Scyphozoan species, Catostylus perezi and Rhopilema hispidum, which swarmed in and around the Gulf of Kutch. Jellyfishing operations were small-scale and operated by motorised crafts, primarily using scoop nets. The fishing season fluctuated between March-May and October-December. The jellyfish landings from November 2017 to February 2020 were 13569.95 metric tonnes (82.1% C. perezi and 17.9% R. hispidum ) of oral arms contributed by Jakhau (67.37%) and Okha (32.63%) jellyfish focal stations, making it a nascent small-scale commercial fishery, which indicates a shift in harvest from fish to jellyfish. In 2018, the estimated value of landed jellyfish (6538.4 metric tonnes) at first sale was ₹78.46 million ($1.14 million). The jellyfishing closures due to socio-sectoral conflicts and unsuitable weather conditions were considered for a 30.71% reduction in 2019. After processing using salt and alum, the semi-dried oral arms of C. perezi and R. hispidum were locally traded as salted-banana-jhar and salted-flower-jhar, respectively. The majority (65%) of processed jellyfish were exported to China, and the rest to other Asian countries from Mundra and Pipavav ports. The myriad challenges were discussed in the nascent jellyfish fisheries. A conceptual plan was advised for developing jellyfish research as a priority area in India that may help minimise knowledge gaps and support management actions. The study recommended jellyfish as future food and secondary raw material with better harvesting and processing practices. A co-management with a precautionary approach was suggested for the sustainability of jellyfish resources. Highlights: Jellyfishing for two native species viz. Catostylus perezi and Rhopilema hispidum . Unreported jellyfishing started in 2000; became a target fishery since 2005. Landed jellyfish (6538.4 metric tonnes) valued $1.14 million at first sale in 2018. Majority (65%) was exported to China and the rest to other Asian countries. Baseline information supports policy formation for nascent jellyfish fisheries.